The research finding of marine fungi as milkfish feed and its utilization for biotechnology digital magazine - Rida Oktorida Khastini; Aditya Rahman Kintu Nihan; Dewi Murni; Susi Martiani (Intelektual Pustaka Media Utama, 2023)
This study aimed to determine the utilization of research results of the selection of marine fungi for milkfish (Chanos chanos) feed. The study was conducted in stages, starting with identifying the issues in the learning activities of biotechnology concepts, followed by experiments to identify research methods and products, selecting an adaptation of research findings as the learning source content, and application and development of research findings as learning. The data and information were gathered through an interview grid and a questionnaire, and the findings of the surveys were then analyzed qualitatively. The results of a selection study of marine fungi from Dua Island, Banten, Indonesia as feed for milkfish related to basic competency (KD) 3.10 and 4.10 can be used as learning resources as digital magazines for class XII high school students. Thus, media can help student in learning process.